Production and Sales Risks in the Manufacturing Sector: The Role of Electricity Supply, Inflation and Fuel Price Volatility - Habanabakize, Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2021)
The manufacturing sector occupies a critical position in the South African economy. However, in recent decades this sector experienced significant instability due to challenges within macroeconomic indicators. The sector's challenges include the issue of electricity distribution, growing inflation rate and commodities price instability. This study aims to assess the effects of electricity supply, inflation and fuel prices on food and beverage production and sales in the manufacturing sector. To this end, the study applied different econometric approaches such as Johansen test for cointegration, vector error correction model (VECM) and Granger causality test on a monthly time series data ranging between January 2002 and December 2019. The study findings suggested the existence of a joint long-run relationship between electricity distribution, inflation rate, fuel price and production and sales of both food and beverage within the manufacturing sector. The result also indicated that both electricity supply and inflation highly impact the production of food and beverage sales compared to the effect of petrol price. Granger causality results have shown that inflation rate can serve in predicting short term production and sales of food and beverage in the South African manufacturing sector. Given the aforementioned findings, the study suggested that to increase production and sales of food and beverage in the manufacturing sector, policymakers should reduce tax on imported fuel. This would assist in lowering petrol prices that may have a repercussion on the inflation rate. Additionally, besides the government support towards electricity production in the Eskom, more effort and resources (financial) would also be allocated to generate and improve other sources of energy such as solar, wind, gas and biogas. Keywords: inflation, Eskom, electricity, fuel price, manufacturing, South Africa JEL Classifications: L60, E31, L11 DOI: https://doi.org/10.32479/ijefi.12509